The features of pedagogical assistance to the personal and professional self-development of a university teacher - Masych, S (Problems of Engineer-Pedagogical Education, 2019)
The article describes the features of pedagogical assistance to the personal and professional selfdevelopment of university teachers in the process of lifelong education. Pedagogical assistance is defined as a system of targeted joint activities of mentors and teachers aimed at improving the effectiveness of their personal and professional self-development in various types of professional activities. The paper defines the laws (entropic equilibrium of human development; the conditionality of the vector of personal and professional self-development by the cultural and educational environment of the institution of higher education, etc.) and the principles (efficiency and facilitation; activity, definition of the goal and dialogue, development and motivational conditionality; subjectivity, etc.) of this process. It is indicated that the regularities of pedagogical assistance to the personal-professional self-development of a teacher will determine the relevant principles as key statements regarding the nature, properties and features of the reality being studied; and will define the direction and conceptuality of personal and professional self-development of the teacher in the process of continuous education.